The Role of Wind Power Plant in Energy Transition towards Net Zero Emission - Judijanto, Loso; ZM, Ajub Ajulian; Winardi, Bambang; Joni, Joni (Westscience Press, 2025)
This literature review explores the role of wind power plants in the global transition towards zero emissions, synthesizing insights from 20 Scopus-indexed articles. The review highlights technological advancements in turbine design, offshore wind power, and energy storage solutions, which enhance wind power efficiency and reliability. It also examines the critical role of supportive policies, such as feed-in tariffs and power purchase agreements, in fostering wind energy growth. Environmental impacts, particularly regarding wildlife and ecosystem disruptions, are considered, alongside strategies to mitigate these effects. Furthermore, the economic viability of wind power is assessed, with a focus on cost reduction, job creation, and local economic development. Finally, the integration of wind power into existing energy grids is discussed, emphasizing the need for grid modernization and storage solutions. The review concludes that wind power is a central component of a zero-emissions energy system, though challenges remain in its widespread adoption and integration.